Hubungan Sistem Informasi Dan Dukungan Keluarga Terhadap Seks Bebas Pada Remaja di SMK 1 Bungoro - Sri Ayu Nata (Jurnal Sains dan Kesehatan, 2020)
Information Technology is a medium that can convey information. Family support is the treatment given to a family member. Casual sex among teenagers is a type of juvenile delinquency that is committed without a marriage relationship. The purpose of this research is to analyze the relationship between information systems and family support for free sex among teenagers at SMK 1 Bungoro. This type of research is analytical survey research, with a cross-sectional design. This research was conducted in March 20 - May 10 2020 Based on the research conducted, the results showed that there was a relationship between information technology and knowledge of free sex (0.05=0.05) and there was no relationship between family support and knowledge of free sex (0.06>0.05). Teenagers are expected to be active in seeking positive information from various existing media so that students have high knowledge and understanding about free sex in order to avoid the risks and impacts caused by free sex.